If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-10g+1=2g-11
We move all terms to the left:
-10g+1-(2g-11)=0
We get rid of parentheses
-10g-2g+11+1=0
We add all the numbers together, and all the variables
-12g+12=0
We move all terms containing g to the left, all other terms to the right
-12g=-12
g=-12/-12
g=1
| a+70=5a+38 | | -2p+8+3p=16 | | 10y+75=50 | | 4y-25=6y-77 | | 100.2+x=140.4 | | 9x+3x+9x=6+8x+11 | | 0.25(3x-8)=2(0.5x+4 | | 2x+(3x+13)=108 | | 6a-14=5a | | 0=64-t-5t^2 | | 9/5c+32=41 | | -15x+4=2x+81 | | 41=9/5c+32 | | (130-7x)=(20+3x) | | 5x-3x=5-2 | | 59+2x=115 | | 628+124m=1504 | | Y=7x-290 | | (6x+1)/(2x-1)=5 | | (7+2x)/2=5 | | 4-3(p+2)=2(p-4) | | 5x+3x=5-2 | | x+88=121 | | k.12=-5k-3 | | -8x+2=28 | | (6x+1)/(2x-1)=9 | | 0.5(5-7x=8-1(4x+6) | | 4+3(w-9)=-12 | | P(x)=-6x-9 | | 5x+3x=2+5 | | 7x−9=4x | | 43+8p=p+21 |